Variabilidade dos atributos de um latossolo vermelho sob plantio direto no cerrado brasileiro e produtividade da soja - Montanari, R.; Lima, R. C. [UNESP]; Bonini, A. S. [UNESP]; Marques, L. S. [UNESP]; Minguini, R. [UNESP]; Carvalho, M. P. [UNESP]; Paz Ferreiro, J.; Costa, N. R. [UNESP] (My University, 2011)
The spatial variability of several soil attributes (bulk density, penetration resistance, water content, organic matter content and pH) as well as soybean yield have been assessed during the 2007/08 growing season, in Selviria (MS) in a Hapludox (Typic Acrustox), under no tillage. The objectives were to assess the spatial variability of soil and plant parameters at the small plot scale and to select the best soil attribute explaining most the variability of agricultural productivity. Soil and plant were sampled on a grid with 121 points within a plot of 25,600 m 2 in area and slope of 0.025 mm -1 slope. Medium and low coefficients of variation were obtained for most of the studied soil attributes as expected, due to the homogenizing effect of the no-till system on the soil physical environment. From the standpoint of linear regression and spatial pattern of variability, productivity of soybeans could be explained according to the hydrogen potential (pH). Results are discussed taken into account that the soybean crop in no-tillage is widely used in crop-livestock integration on the national scene.
Variability of the features of a red latosol on direct yield in a Brazilian cerrado and soybean productivity
Keywords: Kriging; Precision agriculture; Soil management; Soil quality; agricultural production; bulk density; cerrado; crop yield; growing season; kriging; mixed farming; penetration; pH; precision agriculture; red soil; soil management; soil organic matter; soil quality; soil water; soybean; spatial variation; water content; zero tillage; Brazil; Glycine max